Enduring Legacy: Proud Roots in an Uncertain Land - Sand Mohammad Salhout; F. Robert Buchanan (Administrative Sciences)
Siniora Food Industries of Palestine was facing a strategic dilemma. They had sold packaged meats for over 100 years in a challenging and risky environment. Siniora had carved a path of growth, expansion, and development, showcasing the power of endurance. Initially sold by local shopkeepers, the company’s products had gone from local to regional. Publicly traded on the Jordan exchange, Siniora had become a famous brand in Jordan, the Gulf region, UAE, and Saudi Arabia. They used export as well as wholly-owned subsidiary manufacturing facilities. Siniora management considers currently stalled profitability, possible strategies, and risk as the case opens. They dream of a bold move that could span the Asian continent and take the company to the next level. Of course, such a failure could be catastrophic. What are some strategies that would be suggested? Furthermore, can we devise a thorough action plan considering the geopolitical context?